Symbolic Meaning of Local Wisdom in the Slope of Mount Lawu:: An Etnographic Study on Dukutan Village Clean-Up Ceremony - Anindyarini, Atikah; Sumarwati, Sumarwati; Suryanto, Edy; Slamet, Slamet; Maaliki. H, Maulana Danar (Humaniora: Journal of Indonesia Culture and Society, 2024)
The research aimed to describe the procession of the Dukutan village clean-up ceremony, sesaji and its equipment, and its symbolic meaning. The research was conducted using an ethnographic approach. Data sources were events, sesaji and its equipment, cultural observers, and ceremony performers. The sampling techniques used were purposive sampling and snowball sampling techniques. The techniques used to collect data were observation and in-depth interviews. Data validity test was conducted using source and method triangulation techniques. Data analysis was done using an interactive model. The results are, firstly, symbolic meanings of the procession are (a) cleaning-up in Menggung Site symbolizing respect to Narotama, (b) collection sesaji symbolizing the meaning of commonness and gratitude expression, (c) parade symbolizing environment-monitoring behavior, and (d) brawl symbolizing a conflict between Nglurah Lor and Nglurah Kidul. Secondly, symbolic meanings of sesaji are (a) tumpeng of corn rice, symbolizing human-to-God relationship, (b) ares and tempe bakar, symbolizing simplicity, (c) gandik symbolizing wellbeing, and (d) boiled food made of palawija symbolizing natural wealth. Thirdly, other equipments include (a) encek, symbolizing human beings’ submission to God, (b) kendi or vessel containing water, symbolizing the source of living, (c) iket, symbolizing a medium to expel evil spirit, and (d) incense smoke symbolizing behavior to remove badness. Generally, the symbolic meaning found in the research is related to social harmony and environmental conservation.